2017
DOI: 10.1016/j.yebeh.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of inter- and intrastrain differences in mice and rats and their implications for models of seizures and epilepsy

Abstract: It is becoming increasingly clear that the genetic background of mice and rats, even in inbred strains, can have a profound influence on measures of seizure susceptibility and epilepsy. These differences can be capitalized upon through genetic mapping studies to reveal genes important for seizures and epilepsy. However, strain background and particularly mixed genetic backgrounds of transgenic animals need careful consideration in both the selection of strains and in the interpretation of results and conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 210 publications
(323 reference statements)
3
52
0
Order By: Relevance
“…For investigators wishing to evaluate investigational agents or pursue pharmacologic studies for specific patient populations, we encourage the implementation of these CRFs and CDEs with adjustments for the specific model at hand. Moreover, although every effort is made to be thorough in these model summaries and CDEs/CRFs, we understand that variability can arise because of region, diet, humidity, animal vendor, and so on, and can contribute to lab‐to‐lab variability . Thus, in all aspects of model implementation and development, we strongly encourage that the criteria for any model be independently reviewed and refined within each laboratory, using these CDE/CRFs to guide implementation.…”
Section: Rationale For Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For investigators wishing to evaluate investigational agents or pursue pharmacologic studies for specific patient populations, we encourage the implementation of these CRFs and CDEs with adjustments for the specific model at hand. Moreover, although every effort is made to be thorough in these model summaries and CDEs/CRFs, we understand that variability can arise because of region, diet, humidity, animal vendor, and so on, and can contribute to lab‐to‐lab variability . Thus, in all aspects of model implementation and development, we strongly encourage that the criteria for any model be independently reviewed and refined within each laboratory, using these CDE/CRFs to guide implementation.…”
Section: Rationale For Model Selectionmentioning
confidence: 99%
“…Moreover, although every effort is made to be thorough in these model summaries and CDEs/CRFs, we understand that variability can arise because of region, diet, humidity, animal vendor, and so on, and can contribute to lab-to-lab variability. [12][13][14] Thus, in all aspects of model implementation and development, we strongly encourage that the criteria for any model be independently reviewed and refined within each laboratory, using these CDE/CRFs to guide implementation. This is to say, for example, if a median convulsant dose of pentylenetetrazol (PTZ) is needed by an individual lab, we suggest first evaluating the time and dose response to the desired endpoint in the animal strain of interest prior to selecting the PTZ dose and timing of administration.…”
Section: Key Pointsmentioning
confidence: 99%
“…8,9 High-intensity acoustic stimuli induce audiogenic seizures (Sz) in DBA/1 mice, which begin with wild running behavior and proceed to tonic seizures, which are followed by seizure-induced respiratory arrest (S-IRA) that results in death in the immediate postictal period. 8,9 High-intensity acoustic stimuli induce audiogenic seizures (Sz) in DBA/1 mice, which begin with wild running behavior and proceed to tonic seizures, which are followed by seizure-induced respiratory arrest (S-IRA) that results in death in the immediate postictal period.…”
Section: Introductionmentioning
confidence: 99%
“…DBA/1 mice are a chronically susceptible and reliable animal model of SUDEP that shows an inherited and abnormally high degree of seizure-induced death in response to electroconvulsive shock, hyperthermia, convulsant drug, and acoustic stimulation. 8,9 High-intensity acoustic stimuli induce audiogenic seizures (Sz) in DBA/1 mice, which begin with wild running behavior and proceed to tonic seizures, which are followed by seizure-induced respiratory arrest (S-IRA) that results in death in the immediate postictal period. Timely mechanical support of respiration can consistently reverse S-IRA in this SUDEP model.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity in anxiety or cognitive performance at baseline in rodents and its potential consequence for subsequent induction of epilepsy, associated comorbidities, and drug response are not a new observation but have been known for decades. 17 For instance, Adamec et al 18,19 reported interindividual differences in the premorbid affective state of male Wistar rats that contributed to the behavioral effects of amygdala kindling. Their experiments suggested that premorbid anxiety state interacts with amygdala kindling to determine behavioral outcome, and that the outcome may be either anxiogenic, anxiolytic, or no effect at all depending on the level of anxiety at the time of kindling.…”
Section: Diversit Y Is Not a New Phenomenon In Epilepsy Modelsmentioning
confidence: 99%